Assessment of Postural Control and Proprioception Using the Delos Postural Proprioceptive System - Roberto Tedeschi (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Proper postural control and proprioception are essential for maintaining balance, preventing falls, and performing daily activities. Traditional methods of assessing postural control and proprioceptive function often lack objectivity and precision. The DPPS offers a promising solution by providing a quantitative and comprehensive evaluation of postural stability and proprioceptive performance.